Peningkatan Kinerja UKM Percetakan Cabe Kecik Menggunakan Metode Balance Scorecard (BSC) - Heriyanto; Meylinda Mulyati (Universitas Katolik Musi Charitas, 2019)
The result of observations made that the performance of SMEs is still a problem, where in the bookeeping process, SMEs is still manual, namely recording all income and expenditure from SMEs and SMEs owners have never studied the level of performance and profitability, besides that there is a problem in the promotion media which is front of the shop and hanua prom mouth between owners and customers. Implementation of which includes financial aspects (financial) namely to provide discounted promos for permanent customers, provide prices for products that are relatively cheap and update flows into the Ms.Excel while from non financial aspects (customers), namely providing the best and fastest service, producing quality produts, and registering SMEs to online shopping media accounts. SMEs income before implementation amounted to 56.4% with performance value of 70.5% and after implementation at 83.5% with performance value of 96.4% while non-financial (customer) was 87.8% and after implementation 96.4%.